Inspection of the quality of fresh fish at the main market of the Amazon Capital, Manaus-AM (Research, Society and Development, 2022)
Fish is a food that brings health benefits considering its high nutritional value, as its presence in the body enables the strenghtening of the immune system. Its freshness and quality become important to ensure the product’s safety for the consumer. It is a food of simple composition, requiring extra care in its capture, transportation, handling and storage. Therefore, the following research aims to analyze the quality of fresh fish and collect data related to the common hygienic conditions of the main market in the Amazon Capital. Analyses of the conformities and nonconformities of 5 fish from different market fishmongers were made, from which the data obtained in the sensory analysis of fresh fish’s quality were 53% nonconforming items and 47% conforming items. According to the results, the present study aimed to show the importance of the inspection of the markets so that the hygiene and food safety guidelines are followed, as the Good Hygiene and Safety Practices guarantee the product’s quality control, avoiding the risks of food contamination, besides helping to lessen the proliferation of diseases related to the ingestion of contaminated food.